2023
DOI: 10.3390/jpm13071109
|View full text |Cite
|
Sign up to set email alerts
|

Using Anatomy-Based Fitting to Reduce Frequency-to-Place Mismatch in Experienced Bilateral Cochlear Implant Users: A Promising Concept

Abstract: Fitting cochlear implant (CI) users can be challenging. Anatomy-based fitting (ABF) maps may have the potential to lead to better objective and subjective outcomes than conventional clinically based fitting (CBF) methods. ABF maps were created via information derived from exact electrode contact positions, which were determined via post-operative high-resolution flat panel volume computer tomography and clinical fitting software. The outcome measures were speech understanding in quiet and noise and self-percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…[2][3][4][5]7 This improvement with increased cochlear coverage and AID is likely due to the increased tonotopic coverage achieved with longer arrays, where an AID of greater than 600 is generally required to reach tonotopic frequencies below 250 Hz at both the BM and the spiral ganglion. 15,41,43 Several studies have reported electrode translocation from the ST to the SV at 180 . 24,[59][60][61] Possible explanations in the literature include: (1) the vertical trajectory of the ST in some cochleae may be prone to translocation, as proposed by Avci et al 16 ; (2) the decrease in area of the ST over the course of the cochlea; and (3) the friction forces may increase at 180 until the end of insertion, as proposed by Torres et al 62 The current analysis suggests another potential explanation for an increased risk of translocation at 180 may be the tilt of the ST, and the associated tilt of the BM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5]7 This improvement with increased cochlear coverage and AID is likely due to the increased tonotopic coverage achieved with longer arrays, where an AID of greater than 600 is generally required to reach tonotopic frequencies below 250 Hz at both the BM and the spiral ganglion. 15,41,43 Several studies have reported electrode translocation from the ST to the SV at 180 . 24,[59][60][61] Possible explanations in the literature include: (1) the vertical trajectory of the ST in some cochleae may be prone to translocation, as proposed by Avci et al 16 ; (2) the decrease in area of the ST over the course of the cochlea; and (3) the friction forces may increase at 180 until the end of insertion, as proposed by Torres et al 62 The current analysis suggests another potential explanation for an increased risk of translocation at 180 may be the tilt of the ST, and the associated tilt of the BM.…”
Section: Discussionmentioning
confidence: 99%
“…9,12,13 Currently, the highest AID is achieved with 31.5 mm lateral wall electrodes which generally reach between 584 4 and 628 14 on average; however, some studies have found insertion depths past 720 . 15 Avci et al 16 conducted a comprehensive set of microcomputed tomography (μCT) measurements on the ST up to two turns (720 ) in 16 cochleae and found large variability in the ST cross-sectional diameter, vertical trajectory, and the ST height. 16 However, these measurements had limited spatial resolution due to the use of μCT, and the apical turn was excluded due to the inability to discern intracochlear structures from fluid.…”
Section: Introductionmentioning
confidence: 99%
“…The Greenwood function, which correlates the frequency of a pure tone and the spatial location in the Organ of Corti was used in this study. Although, CIs can also stimulate the central axons near the spiral ganglion, which implies a modified tonotopy (Stakhovskaya et al, 2007), we believe that the Greenwood has been proved to be a reliable method to estimate the correlation between the frequency assigned to a determined electrode, especially in insertions below 600 • (Kurz et al, 2023). The effect of adaptation over time to changes in any fitting method is well known (Zinfollino et al, 2020).…”
Section: Limitations and Future Directionsmentioning
confidence: 91%
“…Such “bottom-up” approaches stem from the assumption that fittings that provide well-audible stimuli across the full spectrum of covered frequencies would result in the best overall performance. Other approaches focus on imaging techniques, aiming to fit on the base of anatomical features, electrode positioning, and distance from the modiolus in order to leverage the tonotopic organization of the cochlea to prevent frequency drift due to misalignment of the electrode with the spiral ganglion cells (Jiam et al, 2019; Kurz et al, 2023).…”
Section: Introductionmentioning
confidence: 99%